Efficacy of using parasitic wasps to control stable flies in Kansas feedlots - Greene, G.L.; Cilek, J.E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Release of parasitic wasps has resulted in stable fly reductions averaging 28, 42 and 38% for 1991, 1992, and 1993, respectively, with considerable variation from feedlot to feedlot. Costs for parasites plus sampling averaged $.23, $.32 and $.26 per animal during 1991, 1992, and 1993, respectively. Because stable flies are estimated to cause losses of $5.00 to $30.00 per animal, these costs are very reasonable.
Keywords: Beef; Cattle feedlot; Stable fly; Fly parasites; Pest management costs